2013
DOI: 10.1002/phar.1307
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Warfarin Dosing Requirements After Bariatric Surgery in Patients Requiring Long‐Term Warfarin Therapy

Abstract: Weekly warfarin doses decreased in the immediate postoperative period in anticoagulated patients after bariatric surgery but returned to their preoperative doses after approximately 6 months. A similar pattern was not observed in patients in the control group who underwent other types of abdominal surgery. Compared with preoperative anticoagulation control, this resulted in reduced anticoagulation control despite close INR monitoring. If a causal relationship between bariatric surgery and warfarin sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 26 publications
3
42
1
Order By: Relevance
“…PK changes of medications have been exhibited in drugs, such as warfarin, where lower doses were required for the first 6 months postsurgery, and sertraline, which showed a significant decrease in area under the curve (AUC) and maximum serum concentration (Cmax) when compared between LRYGB patients and controls. Several studies have shown that this effect might be transient for some medications, such as duloxetine, midazolam, and more …”
Section: Discussionmentioning
confidence: 99%
“…PK changes of medications have been exhibited in drugs, such as warfarin, where lower doses were required for the first 6 months postsurgery, and sertraline, which showed a significant decrease in area under the curve (AUC) and maximum serum concentration (Cmax) when compared between LRYGB patients and controls. Several studies have shown that this effect might be transient for some medications, such as duloxetine, midazolam, and more …”
Section: Discussionmentioning
confidence: 99%
“…She was again stabilized only after 10 days and a twofold increase in the daily dose . In contrast, a retrospective matched‐cohort study reported reduced daily doses of warfarin in patients following RYGB surgery, although doses were returned to normal after 6 months . After the surgery, dietary changes with reduced ingestion of vitamin K containing foods, weight loss and changes to the GI tract may play a role in alteration of warfarin efficacy and consequently, INR changes.…”
Section: The Effect Of Bariatric Surgeries On the Absorption Of Variomentioning
confidence: 98%
“…One study compared warfarin dosing in 27 patients before and after bariatric surgery (82% post- RYGB and 18% post- GB) to a matched control group of 59 patients undergoing alternative abdominal surgeries 37 . A significant reduction in the median weekly dose of warfarin after bariatric surgery was found, ranging from 7.7 mg/week decrease at days 8–14 after surgery to a 30 mg/week decrease at days 50–56 (p<0.01), though the absolute change in dosing for individual patients varied substantially, ranging from 0 to 40 mg/week in the three months following surgery.…”
Section: Clinical Datamentioning
confidence: 99%